A Critique of the Claims about Mobile Phones and Kerala Fisherman: The Importance of the Context of Complex Social Systems. Issue 1 (5th December 2017) - Steyn, Jacques
Abstract: This paper challenges some fundamental aspects of research and conclusions relating to the use of technology for community development. Views of technology, in this case the mobile phone, as a tool for increased economic welfare are often skewed due to extreme reductionism, ambiguous interview questions and poor data sources. Research of complex social systems or sub‐systems give the wrong answers when reductionist methodologies are used. To demonstrate such shortcomings, the 2007 paper of Robert Jensen serves as an example. His conclusion that mobile phones enable Kerala fishermen to increase their economic welfare is the most cited paper on ICT4D topics, but there are fundamental methodological and logical problems with the claim, while other research came to contradictory conclusions. This critique is presented on many levels: ideological, paradigmatic, methodology, logical, statistical and semantic.